Highly sensitive raman spectroscopy with low laser power for fast in-line reaction and multiphase flow monitoring - Braun, Frank; Gretz, Norbert (Analytical chemistry, 2016)
In process analytics, the applicability of Raman spectroscopy is restricted by high excitation intensities or the long integration times required. In this work, a novel Raman system was developed to minimize photon flux losses. It allows specific reduction of spectral resolution to enable the use of Raman spectroscopy for real-time analytics when strongly increased sensitivity is required. The performance potential of the optical setup was demonstrated in two exemplary applications: First, a fast exothermic reaction (Michael addition) was monitored with backscattering fiber optics under strongly attenuated laser power (7 mW). Second, high-speed scanning of a segmented multiphase flow (water/toluene) with submicroliter droplets was achieved by aligning the focus of a coaxial Raman probe with long focal length directly into a perfluoroalkoxy (PFA) capillary. With an acquisition rate of 333 Raman spectra per second, chemical information was obtained separately for both of the rapidly alternating phases. The experiment with reduced laser power demonstrates that the technique described in this paper is applicable in chemical production processes, especially in hazardous environments. Further potential uses can be envisioned in medical or biological applications with limited power input. The realization of high-speed measurements shows new possibilities for analysis of heterogeneous phase systems and of fast reactions or processes.